Association between care complexity individual factors and older inpatients with COVID-19: a cross-sectional study - Jordi Adamuz; Jordi Adamuz; Jordi Adamuz; Julia González-Vaca; Julia González-Vaca; Maribel González-Samartino; Maribel González-Samartino; Maribel González-Samartino; María-Magdalena López-Jiménez; María-Magdalena López-Jiménez; María-Magdalena López-Jiménez; Andrea Urbina; et al. (Frontiers in Aging)
BackgroundMany elderly people required hospitalization during the pandemic period, but broader care complexity factors have not been studied in this population. This study aimed to identify the care complexity factors according to age in older people hospitalized with COVID-19.MethodsA multicenter cross-sectional study was conducted from 1 March 2020 to 31 March 2022 at eight public hospitals in Spain. All older patients hospitalized with COVID-19 were classified in the following groups: young-old (65–74 years), middle-old (75–84 years), and oldest-old (≥85 years). The main variable was care complexity individual factors (CCIFs), which included 27 CCIFs classified in four domains: comorbidity/complications, psycho-emotional, mental-cognitive, and sociocultural. Multinomial logistic regressions were performed to identify the association of each CCIFs with age group.ResultsA total of 5,658 admissions were included. Of these, 46.3% were young-old (65–74 years), 34.8% middle-old (75–84 years) and 18.8% oldest-old (≥85 years). The analysis shows that middle-old (75–84 years) patients were associated with chronic disease, position impairment, urinary or fecal incontinence, anatomical and functional disorders, vascular fragility, involuntary movements, fear or anxiety and mental status impairments. Extreme weight, communication disorders, aggressive behavior, agitation and perception reality disorders were additional factors associated with the oldest-old (≥85 years) inpatients with COVID-19. The median number of CCIFs was higher in the oldest-old than in the other age groups (four in young-old [65–74 years]; six in middle-old [75–84 years]; seven in oldest-old [≥85 years] [OR:2.9; 95%CI:2.8–3.1; p < 0.001]).ConclusionThe oldest groups of patients (≥75 years) admitted with COVID-19 had more CCIFs than the young-old group. CCIFs should be included in patient assessment in order to identify care needs in older hospitalized patients.